2019
DOI: 10.29271/jcpsp.2019.10.954
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Deep Breathing Exercises and Incentive Spirometry on Arterial Blood Gases in Second Degree Inhalation Burn Patients

Abstract: Objective: To find out the effectiveness of the deep breathing exercises and incentive spirometryon arterial blood gases in second degree inhalation burn patients. Study Design: Randomised control trial. Place and Duration of Study: The study was conducted in the Burns Unit of PIMS Hospital, Islamabad from September 2017 to March 2018. Methodology: The data was collected on structured questionnaire using respiratory distress scoring and objective tools including arterial blood gases (ABGs) and vital signs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…They found that physiotherapy (respiratory physiotherapy, limb exercises, and peripheral muscle training) improved the quality of life in those patients. In addition, the results of the current study agree with the results of Malik and Tassadaq (10) , who investigated the benefits of deep breathing exercises on arterial blood gases in patients with pulmonary complications. They found that deep breathing exercises are significant in improving Pao2 and decreasing Paco2 in patients with respiratory problems.…”
Section: Discussionsupporting
confidence: 91%
“…They found that physiotherapy (respiratory physiotherapy, limb exercises, and peripheral muscle training) improved the quality of life in those patients. In addition, the results of the current study agree with the results of Malik and Tassadaq (10) , who investigated the benefits of deep breathing exercises on arterial blood gases in patients with pulmonary complications. They found that deep breathing exercises are significant in improving Pao2 and decreasing Paco2 in patients with respiratory problems.…”
Section: Discussionsupporting
confidence: 91%
“…Significantly low values of lung diffusing capacity in patients with smoke inhalation injury confirm the inhalation injury has an impact on the proof of gas exchange [ 29 ]. Deep breathing exercises are more effective in improving the ventilatory function in patients with inhalation injury than incentive spirometry exercises [ 39 ]. The improvement of ventilatory function was confirmed by significant differences of Dlco, and the similar results to the previous study were confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the results showed that the incentive spirometry method was more effective than the DBE method in improving respiration and arterial SaO2. Despite these results, the ndings of another study showed that the two therapies were equally effective in improving arterial blood gases, but DBEs, in particular, were more effective in improving arterial blood gases [19]. The results of another study showed that the DBEs and incentive spirometry are equally effective in reducing the incidence of postoperative chest complications [20].…”
Section: Discussionmentioning
confidence: 99%
“…Results of another study on patients CABG showed no statistically signi cant difference between DBE and incentive spirometry groups in terms of postoperative maximal respiratory pressures, spirometric variables, and SaO2 [5]. This discrepancy can be attributed to the difference in the research populations because some of the aforementioned studies have been performed on patients with second degree burns [19], and the elderly undergoing abdominal surgery [20].…”
Section: Discussionmentioning
confidence: 99%